2020
DOI: 10.1177/1747021819899533
|View full text |Cite
|
Sign up to set email alerts
|

The hand-lateralization of spatial associations in working memory and long-term memory

Abstract: Spatial-numerical and spatial-positional associations have been well documented in the domains of numerical cognition and working memory, respectively. However, such associations are typically calculated by directly comparing (e.g., subtracting) left- versus right-hand responses; it remains an open question whether such associations reside in each hand individually, or are exclusively localised in one of the two hands. We conducted six experiments to investigate the hand-lateralization of both spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Human brain behaviors exhibit significant lateralization (Ocklenburg et al, 2014), including language (Ocklenburg et al, 2013;Yazbek et al, 2020), visuospatial (Vogel et al, 2003;Tokgoz et al, 2020), memory (Babiloni et al, 2006;Zhou et al, 2020), attention (Duecker et al, 2013), and emotional processing (Lindell, 2013). Anatomically, the brain basis of these lateralized behaviors is supposed to be associated with prominent structural asymmetries, including the lateral fissure (Rubens et al, 1976;Toga and Thompson, 2003;Essen, 2005) and the supratemporal sulcus (Shapleske et al, 1999;Hirayasu et al, 2000); however, the structure and the function of lateralization behavior, such as the handedness, is still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Human brain behaviors exhibit significant lateralization (Ocklenburg et al, 2014), including language (Ocklenburg et al, 2013;Yazbek et al, 2020), visuospatial (Vogel et al, 2003;Tokgoz et al, 2020), memory (Babiloni et al, 2006;Zhou et al, 2020), attention (Duecker et al, 2013), and emotional processing (Lindell, 2013). Anatomically, the brain basis of these lateralized behaviors is supposed to be associated with prominent structural asymmetries, including the lateral fissure (Rubens et al, 1976;Toga and Thompson, 2003;Essen, 2005) and the supratemporal sulcus (Shapleske et al, 1999;Hirayasu et al, 2000); however, the structure and the function of lateralization behavior, such as the handedness, is still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on brain plasticity show that learning and training can change the activation status of different brain areas ( Kasahara et al, 2013 ; Zhou et al, 2020 ). The findings of this study are consistent with the existing research results.…”
Section: Discussionmentioning
confidence: 99%
“…We used saccadic responses because they allow to separate the responses along the true horizontal and vertical spatial axes by placing gaze trigger keys to the left and right, and also below and above the centre of the screen. Moreover, saccadic responses do not induce a near-far dimension (as it is the case for manual responses along the sagittal axis, or for up/down keys located below the screen), and they do not induce a left/right hand confound for the up/down responses, all of which can bias spatial associations (Chen et al, 2015;Hartmann, Gashaj, et al, 2014;Santens & Gevers, 2008;Wiemers et al, 2017;Zhou et al, 2019Zhou et al, , 2020. Thus, saccadic responses overcome critical issues that were observed in previous studies that used manual responses.…”
Section: 3mentioning
confidence: 95%
“…emergence of spatial association effects (both SPoARC and SNARC) has recently been highlighted by Zhou et al (2020). They concluded that left-hand responses are more sensitive to spatial-positional associations.…”
Section: Drt Analysesmentioning
confidence: 98%
See 1 more Smart Citation